Fibrin Detected in Plasma of Patients with Disseminated intravascuiar Coagulation by Fibrin-specific Antibodies Consists Primarily of High Molecular Weight Factor XIIIa-crosslinked and Plasmin-modified Complexes Partially Containing Fibrinopeptide A - Pfitzner, Susanne A; Dempfle, Carl-Erik; Matsuda, Michio; Heene, Dieter L (Thrombosis and Haemostasis, 1997)
Pooled plasma from 40 patients with severe disseminated intravascuiar coagulation (DIC) secondary to septic conditions was subjected to gel permeation chromatography on Sephacryl S-500 HR after sample pretreatment with KSCN for dissociation of non-covalent fibrin complexes. Fibrin antigen in eluates was detected by an array of ELISA tests, using two monoclonal antibodies against fibrin degradation product D-dimer, a monoclonal antibody against an epitope generated by plasmin cleavage of the D-domain, and an antibody against the neo-N- terminus of the α-chain of fibrin exposed by cleavage of fibrinopeptide A. Tag antibodies were a polyclonal antibody against the fibrinogen/ fibrin D-domain, a POD-conjugated version of the monoclonal antibody against fibrin α-chain neo-N-terminus, and a polyclonal antibody against fibrinopeptide A. Most fibrin-related material present in the pooled DIC plasma was of higher molecular mass than fibrinogen. Fibrin polymers were reactive with antibodies against D-dimer, plasmin cleaved D-domain, and fibrin α-chain neo-N-terminus. Part of the polymers reacted with antibodies against fibrinopeptide A, indicating presence of fibrinogen or desA-fibrin monomer within the covalently linked complex. In conclusion, the primary analytes detected by monoclonal antibodies for D-dimer, plasmin-specific epitopes of fibrin degradation products, as well as sites exposed by fibrinopeptide cleavage in plasma from patients with disseminated intravascuiar coagulation are high molecular weight factor XIIIa-crosslinked fibrin complexes, containing plasmin-cleaved D-domains, intact fibrin monomer units, and fibrinogen or desA-fibrin monomer.